Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12149-017-1219-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging in musculoskeletal infections with 99mTc-UBI 29-41 SPECT/CT

Abstract: Objective To determine the added value of CT over planar and SPECT-only imaging in the diagnosis of musculoskeletal infection using 99m Tc-UBI 29-4. Materials and methods 184 patients with suspected musculoskeletal infection who underwent planar and SPECT/CT imaging with 99m Tc-UBI 29-41 were included. Planar, SPECT-only and SPECT/CT images were reviewed by two independent analysts for presence of bone or soft tissue infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Conducting research has been shown to facilitate the adoption of new techniques in small-scale initiatives [28]. Given the recent development of infection-specific radiopharmaceuticals such as 99mTc-UBI [29], advances in SPECT quantification and standardisation of imaging procedures [30], the approaches to raise awareness about NM infection imaging and its potential adoption are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting research has been shown to facilitate the adoption of new techniques in small-scale initiatives [28]. Given the recent development of infection-specific radiopharmaceuticals such as 99mTc-UBI [29], advances in SPECT quantification and standardisation of imaging procedures [30], the approaches to raise awareness about NM infection imaging and its potential adoption are needed.…”
Section: Discussionmentioning
confidence: 99%
“…While diagnosis of an infectious process is based on clinical and laboratory data, localization can be difficult. Infectionseeking tracers labelled with single-photon-emitting radionuclides include autologous leukocytes [white blood cells (WBC)] labelled with 99m Tc-hexamethylpropyleneamine oxime (HMPAO) or 111 In-oxine [127] and, to a lesser extent, radiolabelled antibiotics, antibodies [128,129], and 99m Tcubiquicidin 29-41 [130]. 67 Ga-citrate is still used in a few scenarios such as osteomyelitis (OM) of the spine or sternum [131][132][133][134].…”
Section: Infectionmentioning
confidence: 99%
“…99m Tc-UBI 29-41 scintigraphy has an excellent diagnostic performance in the evaluation of musculoskeletal infection. The addition of CT morphologic imaging to planar and SPECT-only imaging led to an increase in diagnostic performance and an improvement in diagnostic confidence in differentiating soft tissue from bone infection, as well as a higher inter-observer agreement [26].…”
Section: Imaging Bacteria In Humansmentioning
confidence: 99%
“…Ubiquicidin (UBI) is a cationic human antimicrobial peptide fragment. However, radiolabelled UBI 29-41 is not widely used as a clinical agent due to the lack of a commercial kit approved worldwide for human studies (only available in Mexico), however, there are over 30 clinical studies performed underlying its usefulness in imaging infections [ 25 , 26 ]. Radiolabelled ciprofloxacin, after promising results in animals, when tested in humans, showed very discordant results in terms of specificity and sensibility [ 24 ].…”
Section: Imaging Bacteria In Animal Modelsmentioning
confidence: 99%